New arsenate minerals from the Arsenatnaya fumarole, Tolbachik volcano, Kamchatka, Russia. III. Popovite, Cu5O2(AsO4)2. (2nd January 2018) - Pekov, Igor V.; Zubkova, Natalia V.; Yapaskurt, Vasiliy O.; Belakovskiy, Dmitry I.; Vigasina, Marina F.; Sidorov, Evgeny G.; Pushcharovsky, Dmitry Yu.
Abstract: The new mineral popovite, Cu5O2 (AsO4 )2, was found in the sublimates of the Arsenatnaya fumarole at the Second scoria cone of the Northern Breakthrough of the Great Tolbachik Fissure Eruption, Tolbachik volcano, Kamchatka, Russia. It is associated with ericlaxmanite, kozyrevskite, urusovite, lammerite, lammerite-β, johillerite, bradaczekite, tenorite, hematite, aphthitalite, anhydrite, langbeinite, calciolangbeinite, As-bearing orthoclase, etc. Popovite occurs as prismatic or tabular crystals and as grains up to 0.2 mm in size forming clusters up to 1.5 mm in size and as crusts on basalt scoria or on aphthitalite incrustations. Popovite is transparent with a vitreous to greasy lustre. Its colour is olive green to dark olive-green, but fine-grained varieties are light yellow-green. The mineral is brittle, with Mohs' hardness ∼3½. Cleavage was not observed and the fracture is uneven. D calc is 5.30 g cm –3 . Popovite is optically biaxial (+), α = 1.84(1), β ≈ 1.86, γ = 1.96(1), 2Vmeas = 50(20)°. The Raman spectrum is given. Chemical data (wt.%, electron-microprobe) are CuO 63.28, ZnO 0.56, V2 O5 0.12, As2 O5 35.80, SO3 0.27, total 100.03. The empirical formula, based on 10 O a.p.f.u., is (Cu4.99 Zn0.04 )Σ5.03 (As1.95 S0.02 V0.01 )Σ1.98 O10. Popovite is triclinic, P1̄, a = 5.1450(3), b = 6.2557(3), c = 6.2766(4) Å, α = 100.064(5), β = 96.351(5), γ = 95.100(5)°, V = 196.47(1) Å 3 and Z = 1. The strongest reflections in the powder X-ray diffraction pattern [ d, Å (I)(hkl) ] are 3.715(36)(110, 101), 3.465(43)(11̄1), 2.968(90)(01̄2), 2.927(100)(111), 2.782(31)(1̄02), 2.768(67)(1̄20), 2.513(55)(1̄2̄1) and 2.462(67)(2̄01). Popovite has a novel structure type. Its crystal structure, solved from single-crystal X-ray diffraction data (R = 0.0459), is based on (010) layers forming an interrupted framework. The layer consists of Cu(1)O6 octahedra with very strong Jahn-Teller distortion and Cu(2)O5 and Cu(3)O5 polyhedra. The linkage between the layers is reinforced by isolated AsO4 tetrahedra. Popovite is named in honour of the Russian mineralogists Vladimir Anatol'evich Popov (b. 1941) and Valentina Ivanovna Popova (b. 1941), a husband and wife research team working in the Institute of Mineralogy of the Urals Branch of the Russian Academy of Sciences, Miass, Russia.